Gedogan Music As Estetic Tradition of Farmer People in the Village of Kemiren - Yudha Karyawanto, H; Sarjoko, M; Rahmanto, K D (KnE Social Sciences, 2019)
Gedogan music is a tradition of peasant society created by ancestors earlier. This study examines the problem of the aesthetic form of society and the meaning of art. The object of this study is gedogan music from kemiren village, glagah district, banyuwangi regency, east java, indonesia. This study aims to: (1) study the form of aesthetic tradition of gedogan music, (2) to study the meaning of gedogan music. The research approach used is qualitative approach with ethnomusikologis method. Research on gedogan music with ethnomusicology approach is reviewed in textual and contextual. Textual elements will describe the issues of musical aspects (musical), while the contextual elements will describe the tradition of the community as a supporter of the arts. The results of research on art form include several aspects, namely: (a) its presentation form which is divided into two elements, including musical and literary elements, (b) presentation tools, including: place, time, performer and costume used, and the meaning of gedogan music includes: (a) song poetry, (b) moral message to society, (b) symbols and meaning of gedogan musical clothing. Gedogan music is a tradition of peasant society created by ancestors earlier. This study examines the problem of the aesthetic form of society and the meaning of art. The object of this study is gedogan music from Kemiren village, Glagah district, Banyuwangi regency, East Java, Indonesia. This study aims to: (1) study the form of aesthetic tradition of gedogan music, (2) to study the meaning of gedogan music. The research approach used is qualitative approach with ethnomusicological method. Research on gedogan music with ethnomusicology approach is reviewed in textual and contextual. Textual elements describe the issues of musical aspects (musical), while the contextual elements describe the tradition of the community as a supporter of the arts. The results of research on art form include several aspects, namely: (a) its presentation form which is divided into two elements, including musical and literary elements, (b) presentation tools, including: place, time, performer and costume used, and the meaning of gedogan music including: (a) song poetry, (b) moral message to society, (b) symbols and meaning of gedogan musical clothing. Keywords: Gedogan music, tradition Kemiren, ethnomusicology